2011
DOI: 10.4236/jbnb.2011.22022
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic observation of the intercellular transport of CdTe quantum dot aggregates through tunneling-nanotubes

Abstract: Various inorganic nanoparticles are being considered for applications in life science as fluorescent labels and for such therapeutic applications as drug delivery or targeted cell destruction. It is of importance to understand their intercellular transport behaviors and mechanisms. Here, the intercellular transport of internalized CdTe quantum dot (QD) aggregates through tunneling-nanotubes (TNTs) between human hepatocellular carcinoma cells was studied by time-resolved confocal fluorescence microscopy. TNTs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Streptavidin-coated CdSe/ZnS quantum dots (QDs), as a nanoparticle, were detected along membrane nanotubes of rat cardiac myoblast cells (H9c2) (He et al, 2010). The intercellular transport of CdTe-QD aggregates through tunneling-nanotubes is also reported in another study (Mi et al, 2011). Direct cell-tocell transfer of porous silicon microparticles by means of TNTs is also reported by Ferrati et al (2012).…”
Section: Micro-and Nano-particles Deliverymentioning
confidence: 80%
See 2 more Smart Citations
“…Streptavidin-coated CdSe/ZnS quantum dots (QDs), as a nanoparticle, were detected along membrane nanotubes of rat cardiac myoblast cells (H9c2) (He et al, 2010). The intercellular transport of CdTe-QD aggregates through tunneling-nanotubes is also reported in another study (Mi et al, 2011). Direct cell-tocell transfer of porous silicon microparticles by means of TNTs is also reported by Ferrati et al (2012).…”
Section: Micro-and Nano-particles Deliverymentioning
confidence: 80%
“…Fluorescence microscopy of labeled organelles or molecules, as well as labeling with organelle-specific dyes demonstrated that TNTs allow for direct transfer of cellular components such as organelles, proteins, microRNAs, Ca 2+ , and quantum dots between cells over long Lou et al, 2012b;Mi et al, 2011;Rolf et al, 2012;Thayanithy et al, 2014). TNTs can in certain cases be highways for transfer of organelles, belonging to the endoplasmic reticulum (ER), Golgi and endosomal/lysosomal system as well as mitochondria, between cells (Lou et al, 2012b;Onfelt et al, 2006).…”
Section: Tnt-mediated Transfer Of Cargosmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is worth noting that siRNA transfer is not a simple process of diffusion but rather energy-dependent, motor protein-involving transportation. For instance, kinesin and dynein have been shown to be motor proteins associated with microtubule transport [ 46 ] that can be blocked by azide, an inhibitor of ATP synthesis [ 47 , 48 ]. This assumption stays in line with our observation that g T and P T of siRNA did not correlate either among Cxs with different single channel conductances (see Table 1 ) or in the single Cx series of experiments.…”
Section: Discussionmentioning
confidence: 99%
“…TNTs have been found in several cancer cell lines including glioblastoma [72, 73, 7880], carcinomas [38, 62, 63, 73], ovarian cancer [57, 71, 81–84], breast cancer [17, 57, 59, 81, 82], bladder cancer [16, 54], HeLa [15, 52], human neuroblastoma [17] and mesothelioma cell lines [58, 59, 8587]. Furthermore, Ady et al [85] showed that malignant mesothelioma cells exhibit 20-fold to 80-fold more TNTs as compared to normal mesothelial cells after 72 h in vitro cell culture.…”
Section: Main Textmentioning
confidence: 99%